Randomized clinical trial: a controlled pilot trial of the 5‐HT4 receptor agonist revexepride in patients with symptoms suggestive of gastroparesis. Issue 4 (24th March 2016) - Tack, J.; Rotondo, A.; Meulemans, A.; Thielemans, L.; Cools, M.
Abstract: Background: Gastroparesis is a chronic gastric disorder characterized by delayed gastric emptying without mechanical obstruction, and clinical symptoms as postprandial fullness, early satiety, bloating, nausea, vomiting, and abdominal pain. Prokinetic agents are used for the treatment of gastroparesis. Revexepride, a 5‐hydroxytryptamine (serotonin) receptor (5‐HT4 R) agonist, could be a good candidate drug for the gastroparesis treatment. Aim: In the current phase II, exploratory, double‐blind, randomized, stratified, placebo‐controlled, repeated dose trial (EudraCT number 2007‐004997‐23), the efficacy on gastrointestinal symptoms and gastric emptying rate, safety, and pharmacokinetic profile of three oral doses of revexepride (0.02, 0.1, and 0.5 mg administered orally t.i.d. for 4 weeks) was evaluated in trial participants (diabetic and non‐diabetic) with upper gastrointestinal tract symptoms suggestive for gastroparesis. Methods: Eighty participants, enrolled in four parallel treatment groups, were asked to score their symptom diary data, gastroparesis cardinal symptom index (GCSI), patient assessment of upper gastrointestinal disorders‐symptom severity index (PAGI‐SYM), quality of life questionnaires, and meal‐related symptom score. Gastric emptying rate was evaluated by 13 C‐octanoic acid breath test. Key Results: The severity of the symptoms assessed by means of GCSI and PAGI‐SYM decreased at Week 2 and decreased further at Week 4 in all treatment groups including placebo, with similar trends in all treatment groups. Quality of life improved in all treatment groups after 4 weeks of treatment. No differences on gastric emptying rate were shown between any of the active treatment groups and placebo. Revexepride was generally safe and well‐tolerated. Conclusions & Inferences: Four weeks of revexepride treatment did not improve symptoms or gastric emptying over placebo in patients with symptoms suggestive of gastroparesis. Abstract : Gastroparesis cardinal symptom index over time in patients treated with placebo or three doses of revexepride. Drug doses did not provide additional symptom benefit over placebo.